User-Generated Content as a Strategic Marketing Tool: A Multi-Regional Analysis of Consumer Purchase Decisions and Brand Engagement the Home Industry in the Digital Economy Era - Rolando, Benediktus; Mulyono, Herry (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The proliferation of user-generated content (UGC) on social media platforms has fundamentally transformed consumer purchasing behavior in the fashion industry. This study examines the multifaceted impact of UGC on consumer decision-making processes, brand perception, and purchase intentions through a systematic literature review of 51 peer-reviewed articles sourced from Scopus and Google Scholar databases, representing research from diverse geographical regions including Asia, Europe, North America, and the Middle East. Employing a mixed-methods approach combining qualitative analysis of social media interactions and quantitative assessment of consumer survey data, the research reveals three key findings: (1) UGC significantly enhances brand trust and authenticity, particularly when delivered through peer recommendations and influencer partnerships; (2) consumer engagement with UGC correlates strongly with increased purchase intentions, especially among younger demographics; and (3) the effectiveness of UGC varies based on content format, platform selection, and perceived source credibility. Drawing on this geographically diverse body of literature published between 2019-2024, this study contributes to the growing field of digital marketing research by providing actionable insights for fashion brands seeking to leverage UGC in their marketing strategies, while also highlighting the theoretical implications for understanding modern consumer behavior in the social media era.